International Business: The Challenges of Globalization - John J. Wild; Kenneth L. Wild (New York Pearson Education, 2019)
For courses in international business. Cultural focus helps students understand key concepts in international business International Business: The Challenges of Globalization uses the ever-present and salient subject of culture to present real-world examples and engaging features to bring international business to life and pique student interest . The 9th Edition uses a unique organizing framework that helps students to understand how the elements of international business are related and with a focus on employability skills, students understand how the concepts learned in this course will be relevant to their future careers.The material has been thoroughly updated based on ongoing changes in the international business world to ensure that it remains up-to-date with the rapidily changing world.
Keywords: Business; Nonfiction; Textbooks; International Business and Management (ECO2023-N )